2009
DOI: 10.4322/rbpv.01802007
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e migraÇão de larvas infectantes de ciatostomíneos (Nematoda: Cyathostominae) em gramínea coast cross (Cynodon dactylon) em clima tropical, na Baixada Fluminense, RJ, Brasil

Abstract: ResumoEsse estudo foi realizado no período de julho de 2003 a novembro de 2004, para avaliar o desenvolvimento, a sobrevivência, a migração das larvas infectantes em gramínea "coast cross" (Cynodon dactylon) e o horário de maior disponibilidade, em condições de clima tropical, na Baixada Fluminense, RJ, Brasil. De julho de 2003 a setembro de 2004, massas fecais de equinos naturalmente infectados foram depositadas mensalmente sobre a gramínea. Sete dias após, amostras de fezes e gramínea foram coletadas semanal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…In the current study, the season that presented the highest precipitation (summer) also had the highest EPG counts (Table 1). These results agree with those found by Couto et al [38], who observed that in the rainy season, in tropical climates (high temperature), horses presented higher EPG counts, which may be related to greater egg elimination by female horses when weather conditions are more favorable.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the season that presented the highest precipitation (summer) also had the highest EPG counts (Table 1). These results agree with those found by Couto et al [38], who observed that in the rainy season, in tropical climates (high temperature), horses presented higher EPG counts, which may be related to greater egg elimination by female horses when weather conditions are more favorable.…”
Section: Discussionsupporting
confidence: 93%
“…The type of grass can also affect the number of larvae recovered. Other studies with different grasses in the same study area reported a lower number of larvae recovered from Coast-cross and Tifton 85 pastures (BEZERRA et al, 2007;COUTO et al, 2008;COUTO et al, 2009;QUINELATO et al, 2008;SANTOS et al, 2011) than from Brachiaria humidicola in our study. Pastures are more fibrous and flattened during the dry season and, depending on the management, they can protect L 3 against temperature changes and evaporation (BRADY; WEIL, 1999), providing an ideal microclimate for a prolonged survival.…”
Section: Discussioncontrasting
confidence: 48%
“…Fecal masses play an important role in the development of eggs and larvae, acting as reservoirs for larvae, as observed by Mfitilodze and Hutchinson (1987), Uhlinger (1991), Bezerra et al (2007) and Santos et al (2011). With adequate humidity and temperature, horses can become infected immediately after rainfall, but these animals in this area are more exposed to infection during dry than heavy rainfall periods (BEZERRA et al, 2007;QUINELATO et al, 2008;COUTO et al, 2008;COUTO et al, 2009;RODRIGUES et al, 2008). The environmental conditions of the study area favor the development of infective cyathostomin larvae, i.e., L 3 were present in the pasture during both periods studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation